Implementation of Good Corporate Governance (GCG) Principles in the Management of the Ranaka Sejahtera Bersama Cooperative - Yohanes Y. Mbouk; Indriyati; Kristianus S. H. Molan; Hendrikus L. Kaha; Yasinta Y.P. Peten (Prodi Administrasi Pendidikan, Universitas Pendidikan Mandalika, 2026)
This research uses a descriptive qualitative research method. The informants in this study involved five informants who were selected purposively according to their roles and involvement in management and development activities. The informants consisted of the Head of Supervision, Chair, Secretary, and field officers representing KSP Ranaka members. Data collection techniques included in-depth interviews, observation techniques, and documentation studies. Data analysis was carried out through data reduction, data presentation, and conclusion drawing. The results of the study show that KSP Ranakan Sejahtera Bersama has realized the five principles and needs to develop several improvement strategies, which are the recommendations and conclusions, namely: The principle of transparency has been well implemented, Accountability by controlling challenges related to human resource quality and conflicts, Responsibility requires attention to social/educational programs for members, Independence by continuing to develop and improve the management, Fairness by improving the provision of services and rights to all members with SOPs that are formulated and complied with Credit unions often fail not because there are no rules, but because of weak enforcement of internal rules. Therefore, for other researchers, it is necessary to specifically examine the analysis of opportunities and challenges using SWOT analysis for the development of credit union governance so that it can be competitive, and it is necessary to examine the implementation of GCG using the agency theory and theory approaches. Key Words: Good Corporate Governance (GCG), Principles, Management.